Synthesis of Thiodisaccharides Bearing N‐Acetylhexosamine Residues: Challenges, Achievements and Perspectives. Issue 10 (25th June 2021) - Cristófalo, Alejandro E.; Cano, María Emilia; Uhrig, María Laura
Abstract: Carbohydrate‐protein interactions are involved in a myriad of biological processes. Thus, glycomimetics have arisen as one of the most promising synthetic targets to that end. Within the broad variety of glycomimetics, thiodisaccharides have proven to be excellent tools to study these processes, and even more, some of them unveiled interesting biological activities. This review brings together research made on the introduction of N ‐acetylhexosamine residues into thiodisaccharides to date, passing through classic substitution (as SN 2, thioglycosylation and ring‐opening reactions) and addition (as thiol‐ene coupling and Michael‐type additions) reactions. Recent and interesting developments regarding addition reactions to vinyl azides, cross‐coupling reactions and novel chemoenzymatic methods are also discussed. Abstract : In this review, we collected all the excellent reports made to date on the synthesis of HexNAc‐containing thiodisaccharides. We organised them into three groups taking into consideration the reactions involved in the construction of the thioglycosidic bond: substitution reactions, addition reactions and chemoenzymatic methods.